The Cognitive Awareness Scale for Basic and Instrumental activities of daily living to measure self-awareness after acquired brain injury: Preliminary evidence of its validity - Salazar-Frias, Daniel; Rodriguez-Bailon, Maria; Ricchetti, Giorgia; Navarro-Egido, Alba; Funes, María Jesus (Taylor & Francis, 2023)
Objective: There is a crucial need for reliable tools to measure impaired self-awareness (ISA) in patients with acquired brain injury (ABI) across cognitive-functional domains. The aim of this study was to assess the psychometric properties of the Cog-Awareness ADL Scale, which is a novel self-proxy discrepancy method for measuring ISA in both basic and instrumental activities of daily living. Methods: This multicenter study included 54 patients (no-low ISA n = 33; severe ISA, n = 21) from four outpatient rehabilitation units in Málaga-Granada, Spain, and 51 healthy controls. The participants and proxy raters completed the Cog-Awareness ADL Scale and the Patient Competency Rating Scale (PCRS). Agreement between both scales was assessed using Spearman's correlations and the Bland-Altman plot. Group comparisons were made on measures of SA, cognitive abilities and demographic variables. Sensitivity and specificity were analysed by ROC curve analysis. Results: Convergent validity was supported by strong correlations with the PCRS and its subscales (rho's ranging from 0.51 to 0.80, p < 0.01 for all). The Bland-Altman plot confirmed measurement agreement (only 3.70% of the scores were outside the 95% limits). External validity was demonstrated by effectively discriminating between healthy controls and ABI patients with no-low and severe ISA on each discrepancy index while controlling for cognitive/demographic variables. The Cog-Awareness ADL Scale showed optimal diagnostic accuracy (AUC = 0.95, sensitivity = 0.90, specificity = 0.90). Conclusions: The Cog-Awareness ADL Scale proved to be a feasible, valid, and clinical tool to assess ISA across different cognitive-functional domains, in Spanish ABI-patients.
Keywords: Cerebro - Rehabilitación; Activities of daily living; Self-awareness; Executive functions; Occupational therapy; Executive functions; Neuropsychology; Neuropsychological Assessment